2013 15th European Conference on Power Electronics and Applications (EPE) 2013
DOI: 10.1109/epe.2013.6631965
|View full text |Cite
|
Sign up to set email alerts
|

On-line [T<inf>J</inf>, V<inf>ce</inf>] monitoring of IGBTs stressed by fast power cycling tests

Abstract: This paper describes a part of a larger supervision system able to monitor the on-state voltage V CE and the junction temperature T J of IGBT in operation. That system is associated to an ageing test bench stressing IGBT modules by power cycling. All along the ageing test, it is necessary to supervise V CE , always measured in the same conditions of junction temperature and collector current, in order to detect possible degradations of wire bonds and/or emitter metallization. In addition, the thermal swing amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Another contribution in the literature [13] proposes the circuit of Fig. 2(b), where the DUT disconnection is achieved by adding four switches.…”
Section: Igbt Power Stack Integrity Assessment Methods Formentioning
confidence: 99%
See 2 more Smart Citations
“…Another contribution in the literature [13] proposes the circuit of Fig. 2(b), where the DUT disconnection is achieved by adding four switches.…”
Section: Igbt Power Stack Integrity Assessment Methods Formentioning
confidence: 99%
“…Two of the switches isolate the load during the inverter current interruption and the two other switches allow the load current to freewheel during the interruption. Using the same principle as in [13], the method in [14] combines the V ce methods with sensing and load current for aging detection due to bond-wire lift-off or solder delamination. In this case, the calculation of the thermal resistance for the aging evaluation requires measurements with sinusoidal current at level close to the nominal ratings, at the same temperature conditions, and an extra sensor at baseplate level.…”
Section: Igbt Power Stack Integrity Assessment Methods Formentioning
confidence: 99%
See 1 more Smart Citation
“…In such a paper, it is concluded that the onstate collector-emitter voltage (V CE_ON ) calibrated at low currents seems to be the most suitable TSEP. However, this method is unsuitable for converter applications because the converter operation has to be interrupted in order to do that [8]. If the V CE_ON at high currents is used as TSEP, the junction temperature could be estimated without any interruptions during normal operations.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, for device ageing studies in a laboratory, electrical measurements of device parameters are often used as an indicator of device ageing. Table 1 shows that for most of the degradation modes, on‐state resistance variation and junction temperature increase are frequently observed [6, 7]. For that purpose, smart metal‐oxide semi‐conductor (MOS) technology integrates sensors that permit to measure the on‐state resistance and junction temperature of the device.…”
Section: Introductionmentioning
confidence: 99%